Validity of the Greek Knowledge About Childhood Autism Among Health Workers (KCAHW) Questionnaire - Vasiliki Zarokanellou; Alexandros Gryparis; Evridiki Papagiannopoulou; Vassiliki Siafaka (Psychiatry International)
The study investigates the reliability and validity of the Greek version of the knowledge about childhood autism among health workers (KCAHQ) questionnaire. A total of 541 allied healthcare participants (n1 = 471 students; n2 = 70 professionals) provided their socio-demographic variables and completed the KCAHQ. Analysis showed overall floor-ceiling effects lower than 15% and skewness-kurtosis values between ±2. The internal consistency was good (Kuder–Richardson 21 = 0.80) and all domains were significantly correlated with each other, with Spearman’s coefficients ranging from 0.26 to 0.57. The split-half reliability was satisfactory, with the Spearman–Brown and lambda 4 coefficients equal to 0.618 and 0.613, respectively. All the goodness of fit indices generated by confirmatory factor analysis were acceptable (CFI = 0.88; TLI = 0.861, RMSEA = 0.052). Being a professional, having personal contact with an individual with autism, and having received autism-specific training significantly increased scores on the KCAHW. Overall, the Greek KCAHQ seems reliable and valid; however, domain 4 presents insufficient internal consistency.